CORPORATE GOVERNANCE APPLIED TO SMALL AND MEDIUM-SIZED ENTERPRISES: LIMITATIONS OF TRADITIONAL MODELS AND ADAPTATION PROPOSALS - Rizzo Rocha, Rafael (Revista Gênero e Interdisciplinaridade, 2026)
This article examines, through a systematic literature review, the application of corporate governance practices in small and medium-sized enterprises (SMEs). The investigation focuses on scientific production from the last five years, seeking to understand the inherent limitations of traditional governance models — originally designed to meet the demands of large publicly traded corporations — and to map the adaptation alternatives being developed by the academic community. The research was conducted through a structured search in Scopus, Web of Science, SciELO, and Google Scholar databases, employing qualitative analysis of the selected works. The findings reveal that, although the adoption of formal governance mechanisms in SMEs is still in an embryonic stage, the implementation of adapted practices — notably the promotion of transparency, the establishment of accountability mechanisms, and the constitution of advisory boards — produces significant positive effects. Such practices not only expand the possibilities for raising financial resources but also enhance innovative capacity, strengthen organizational resilience, and increase the competitiveness of these companies. The conclusion points to the absence of a universal governance model applicable to SMEs, making it essential to adopt flexible and gradual approaches that consider the specificities of this business segment: ownership concentration, the lack of distinction between management and ownership, family ties, and resource constraints. Future investigations should prioritize longitudinal studies and behavioral analyses of the actors involved in governance processes.